Place of Azerbaijan Power System in Inter-State and Intercontinental Associations, Adjusting Capabilities of Power Stations and Recommendations on Their Usage - N. А. Yusifov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the place and role of Azerbaijan Power System in the Euro-Asian Power Association which is to be established, power line capacities of inter-state power lines. Justification of construction of new power lines is given in the paper.It contains the characteristics of control systems of steam-turbine, gas- and gas-turbine plants. Level of sufficiency and control efficiency (frequency and power) and satisfactoriness of their characterictics have been analyzed. The conclusions have served as a basis for the works that had been started to develop and technically modernize the control systems.